Surface Properties of Non-conventional Cellulose Fibres - Sfiligoj Smole, Majda; Hribernik, Silvo; Kurečič, Manja; Urbanek Krajnc, Andreja; Kreže, Tatjana; Stana Kleinschek, Karin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The authors describe how sustainable textile fibers from crops such as quinoa, grass, hops, corn and wheat stems, etc. have recently begun to generate great interest. The structure-property relationships of such non-conventional cellulose fibers are studied in this brief, as are their sorption and surface properties which are of primary importance. A systematic review of each fiber's properties is given, the emphasis is placed on the water sorption capacity, the fiber's surface potential, and fibrillation properties.
Introduction -- Anatomy of plant fibres -- Non-conventional plant fibres -- Structure and properties of non-conventional cellulose fibres -- Cellulose nanofibres -- Preparation of cellulose nanocrystals CNC from nettle, weeping willow, balm-leaved archangle, lucerne and Spanish broom -- Conclusion -- References.
Keywords: Polymers; Materials -- Analysis; Surfaces (Physics).; Surfaces (Technology).; Thin films; Polymers; Characterization and Analytical Technique; Surface and Interface and Thin Film; Surfaces, Interfaces and Thin Film